Official Demand for U.S. Debt : Implications for U.S. Real Interest Rates - Kaminska, Iryna (IMF Working Papers; Working Paper, 2014)
By constructing and estimating a structural arbitrage-free model of demand pressures on US real rates, we find that recent purchases of US government debt securities by the Fed and foreign officials have significantly affected the level and the dynamics of US real rates. In particular, by 2008, foreign purchases of US Treasuries are estimated to have had cumulatively reduced long term real yields by around 80 basis points. The subsequent total impact of Fed purchases in 2008-2012 has been even larger: the quantitative easing (QE) has depressed real 10-year yields by around 140 basis points. Our findings also reveal that the Fed policy interventions and foreign official purchases affect longer term real bonds mostly through a reduction in the bond premium.